Prevalence of Methicillin-resistant (MRSA) gene in Staphylococcus aureus isolates expressing PantonValentin Leukocidin (pvl) gene recovered from clinical cases in Rasht hospitals - Houra Pourghafar; Nour Amirmozafari; Masoumeh Amirmozafari (Fasa University of Medical Sciences, 2020)
Background & Objective: Panton-Valentine Leukocidin (PVL) is associated with strains of Staphylococcus aureus that produce a high level of virulence which is characterized by skin abscesses and acute necrosis. Goals: The aim of this study was to investigate the prevalence of pvl gene and its relationship with Methicillin- resistant Staphylococcus aureus (MRSA) in isolated samples taken from hospitalized patients in Rasht, north of Iran. Materials & Methods: During a six-month treatment period, a total of 92 clinical isolates of Staphylococcus were obtained. Initial tests were performed using the Disk Diffusion Method and Methicillin resistance test determined by an Oxacillin disk. In order to elucidate the frequency detection of pvl gene, standard PCR was accomplished using specific primers and then pvl positive isolates were further analyzed for the presence of mecA gene by the use of specific primers in PCR. Result: In total, 18 isolates (19.56%) were shown to be positive in terms of their carrying the pvl gene among which, 15 isolates (83.33%) were MRSA, 3 (16.66%) were MSSA, and 8 (44.44%) were positive for mecA gene. Conclusion: Despite the existence of pvl genes in MRSA isolates, PVL toxin producing strains of Staphylococcus aureus are serious threats for health. So, it seems that achieving a rapid and repeatable method for medical center, will help the timely diagnosis and control of PVL- producing strains.